HOW PHASEOLUS VULGARIS L (CHEAKPEA) CAN REDUCE OF BLOOD SUGAR PRESURE IN TYPE 2 DIABETES MELLITUS - Marta, Arnia Sactya; Hikmawati, Isna; Isnaini, Nur; Ramdani, Meida Laely (Jurnal Kesehatan Masyarakat Indonesia, 2024)
Background: Diabetes over the past 10 decades has increased from 4.7% to 8.5% of the world population, Diabetes Mellitus Type 2 can be controlled by physical activity, diet, consumption of fruits and vegetables. The aim is to determine the effectiveness of chickpea juice on lowering blood sugar in patients with Type 2 Diabetes Mellitus. Methods: Research with quasy experiment design. This sample uses a categorical descriptive formula obtained 22 respondents who are categorized into 22 intervention groups and 22 control groups. Sampling using purposive sampling with inclusion criteria in diabetes millitus patients aged 53 - 77 years. The instrument used in this study used a questionnaire sheet, chickpea juice, and a blood sugar level checker using a blood sugar meter. Data analysis using wilcoxon test with α = 5%. Results: The study showed that most of the elderly were 54.55%, the most gender was female as much as 65.91%. In this study obtained results as many as 5 respondents (11.4%) with normal blood sugar and 17 respondents (38.6%) with hyperglycemia. There is a relationship between blood sugar levels in the intervention group given chickpea juice with a value (ρ value = 0.001, α = <0.005) and a decrease in SD of 94.5 mg/dL. Conclusion: There is a relationship between chickpea juice to reduce blood sugar levels in patients with Type 2 Diabetes Mellitus.